PENERAPAN GAMIFIKASI TERHADAP KETERLIBATAN DAN PEMAHAMAN KONSEP IPAS SISWA SD - Aprilianti, Putri; Didik Tri Setiyoko; Atikah Mumpuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Students conceptual understanding of science learning, particularly light and sound, is still low in fifth grade students at SDN Bulakparen 02. Students appear less active, ask fewer questions, and simply memorize without understanding the concepts. This condition indicates the need for learning media that can increase motivation and learning engagement, one of which is through gamification. This study uses a qualitative descriptive approach to describe how gamification is implemented, how students are engaged during learning, and how the media helps conceptual understanding. Data were collected through observation, interviews, and documentation. The results show that gamification makes learning more interesting, increases students' attention and participation, and helps them understand the concepts of light and sound better. Thus, gamification is an effective strategy to improve the quality of science learning in elementary schools.